2009
DOI: 10.1001/archgenpsychiatry.2008.510
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Functional Variant of Neuronal Nitric Oxide Synthase on Impulsive Behaviors in Humans

Abstract: These findings implicate deficits in neuronal signaling via nitric oxide in moderation of prefrontal circuits underlying impulsivity-related behavior in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
137
2
11

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(161 citation statements)
references
References 58 publications
11
137
2
11
Order By: Relevance
“…Targeted disruption of Nos1 in mice increased impulsivity and aggressiveness, reduced anxiety, and impaired learning (19,20). Human behavioral and imaging studies have shown NOS1 exon 1f-VNTR to be associated with hyperactive, impulsive, and aggressive behavior as well as hypofunctioning of the anterior cingulate cortex (15,21,22).Although the NOS1 gene has been linked to ADHD, impulsivity, and modification of neurotransmitter levels in the striatum, effects of NOS1 genetic variation on striatal activity have not been investigated. The objective of the present study was to better understand the effect of this gene on neurobiological dysfunctioning in adult ADHD by exploring the influence of the exon 1f-VNTR on impulsivity and reward-related striatal activity in a large sample of adult ADHD patients (N=87) and healthy comparison subjects (N=49).…”
mentioning
confidence: 99%
“…Targeted disruption of Nos1 in mice increased impulsivity and aggressiveness, reduced anxiety, and impaired learning (19,20). Human behavioral and imaging studies have shown NOS1 exon 1f-VNTR to be associated with hyperactive, impulsive, and aggressive behavior as well as hypofunctioning of the anterior cingulate cortex (15,21,22).Although the NOS1 gene has been linked to ADHD, impulsivity, and modification of neurotransmitter levels in the striatum, effects of NOS1 genetic variation on striatal activity have not been investigated. The objective of the present study was to better understand the effect of this gene on neurobiological dysfunctioning in adult ADHD by exploring the influence of the exon 1f-VNTR on impulsivity and reward-related striatal activity in a large sample of adult ADHD patients (N=87) and healthy comparison subjects (N=49).…”
mentioning
confidence: 99%
“…Reif et al (2006; have observed a polymorphic promoter dinucleotide repeat length variation of the NOS1 gene (NOS1 Ex1f-VNTR), which may potentially be related to clinical characteristics of impulsive behaviors (Reif et al, 2009). Retz et al (2010) have examined the association between self-reported impulsiveness, venturesomeness and empathy in 182 adult males (young to middle-aged) Caucasian offenders referred to forensic psychiatric medicine; impulsiveness and venturesomeness presenting closely related facets (Eysenck et al, 1990) and empathy involving moral reasoning, prosocial behavior and control of aggression (Eisenberg, 2000;Eysenck et al, 1990).…”
Section: Epigenetic Implications Modulating Impulsiveness: a Case Formentioning
confidence: 99%
“…[81] Reif ve arkadaşlarının yaptığı çalışmada ise DEHB'li hastalarda anormal NOS-1 varyantı tespit edilmiştir. [82] Ceylan ve arkadaşlarının yaptığı bir çalışmada DEHB ile kontrol grubu karşılaştırıldığında nitrik oksit (NO) seviyesi yüksek bulunmuştur. [83] Aynı çalışmada aile hikayesinde DEHB'li bireylerin çok olduğu hasta grubuyla ailesinde DEHB hikayesi negatif olan grupla karşılaştı-rıldığında anlamlılığa yakın olarak (NO) seviyesinin yükselmiş olduğu bulundu.…”
Section: Alfa 1c Noradrenerjik Reseptör Geniunclassified